OBMEP in numbers: A quantitative analysis of the awards of schools in Piauí - Costa, Dalilla Ravene Marques da; Sousa , Adriano Faustino de; Rocha , Daniel Cleberson da Conceição; Silva , Luiz Carlos Araujo da; Silva , Eduardo de Moura dos Santos; Vale , Mardonio Pereira do; Sousa , Raimundo Nonato de; Oliveira , Luiz Gustavo Farias de; Neto , Guilherme Luiz de Oliveira; Oliveira , Edson do Nascimento de; Santos , Felipe de Sousa; Macedo, Gilmar Antonio Ribeiro de (Seven Editora, 2024)
The problem-solving methodology is one of the most studied trends in mathematics education in recent years. Based on this, this article aims to analyze the contributions of this methodology in the teaching of Mathematics through a bibliographic study on the performance indices of students and schools in Piauí in the Brazilian Public School Mathematics Olympiad (OBMEP). The bibliographic references were found through an advanced search on the Oasis Platform, which had three descriptors (Mathematics Olympiads, OBMEP and performance analysis) and generated a result with thirteen journals, which provided the methodological and bibliographic basis for the development of this study. It is justified by its relevant contribution to the understanding of the impact of the Olympiad on the learning and performance of the target students.  Concerning this, this study will prove that the Olympiad studied stimulates interest and improvement in the teaching of Mathematics, the discovery of talents and continuing education, and also expands academic and professional opportunities. DOI:https://doi.org/10.56238/sevened2024.010-016